Endochondral Growth Defect and Deployment of Transient Chondrocyte Behaviors Underlie Osteoarthritis Onset in a Natural Murine Model - Staines, K. A.; Madi, K.; Mirczuk, S. M.; Parker, S.; Burleigh, A.; Poulet, B.; Hopkinson, M.; Bodey, A. J.; Fowkes, R. C.; Farquharson, C.; Lee, P. D.; Pitsillides, A. A. (Arthritis & rheumatology (Hoboken, N.J.), 2016)
Objective To explore whether aberrant transient chondrocyte behaviors occur in the joints of STR/Ort mice (which spontaneously develop osteoarthritis [OA]) and whether they are attributable to an endochondral growth defect. Methods Knee joints from STR/Ort mice with advanced OA and age‐matched CBA (control) mice were examined by Affymetrix microarray profiling, multiplex polymerase chain reaction (PCR) analysis, and immunohistochemical labeling of endochondral markers, including sclerostin and MEPE. The endochondral phenotype of STR/Ort mice was analyzed by histologic examination, micro–computed tomography, and ex vivo organ culture. A novel protocol for quantifying bony bridges across the murine epiphysis (growth plate fusion) using synchrotron x‐ray computed microtomography was developed and applied. Results Meta‐analysis of transcription profiles showed significant elevation in functions linked with endochondral ossification in STR/Ort mice (compared to CBA mice; P < 0.05). Consistent with this, immunolabeling revealed increased matrix metalloproteinase 13 (MMP‐13) and type X collagen expression in STR/Ort mouse joints, and multiplex quantitative reverse transcriptase–PCR showed differential expression of known mineralization regulators, suggesting an inherent chondrocyte defect. Support for the notion of an endochondral defect included accelerated growth, increased zone of growth plate proliferative chondrocytes (P < 0.05), and widespread type X collagen/MMP‐13 labeling beyond the expected hypertrophic zone distribution. OA development involved concomitant focal suppression of sclerostin/MEPE in STR/Ort mice. Our novel synchrotron radiation microtomography method showed increased numbers (P < 0.001) and mean areal growth plate bridge densities (P < 0.01) in young and aged STR/Ort mice compared to age‐matched CBA mice. Conclusion Taken together, our data support the notion of an inherent endochondral defect that is linked to growth dynamics and subject to regulation by the MEPE/sclerostin axis and may represent an underlying mechanism of pathologic ossification in OA.